Assimilation over protection: rethinking mandarin language assimilation in China. (2nd October 2021) - Lin, Cong; Jackson, Liz
ABSTRACT: In the last decades, the propagation of Mandarin has been carried out across the People's Republic of China as de facto language assimilation. It has achieved great success in that over 80 percent of the population can speak Mandarin, but it has also had devastating effects on minority language learning, maintenance, and use. Meanwhile, the Chinese government continues to strongly promote Mandarin nationwide. This paper applies summative content analysis to examine the reasons the government provides for promoting Mandarin in its official policies, government reports, and news. Our findings show that in official documents, the value of promoting Mandarin typically prevails over the importance of protecting minority languages. Additionally, the government tends to equate minority assimilation with progress and advancement. In this context, we argue that to enhance conditions of minorities in society, the government should work to ensure that mastering Mandarin is a free choice of minorities, and regard Mandarin and minority languages and their speakers as of equal status and value in society.